Nilai-Nilai Moral dalam Novel Heartbreak Motel karya Ika Natassa - Manik, Teti Ronaido; Hayati, Yenni (Universitas Negeri Padang, 2024)
This research aims to describe the depiction of moral values in the novel Heartbreak Motel by Ika Natassa. This research uses descriptive qualitative method with data in the form of words, phrases, clauses, and sentences containing moral values in the novel. The results show that there are 68 data containing moral values which are divided into three categories: first, moral values that relate between humans and themselves: surrendering to God, praying, recognizing God's greatness, gratitude, and obedience. Second, moral values that relate between humans and other humans: caring for others, helping, thanking, respecting others, giving advice, and forgiveness. Third, moral values that relate between humans and God: surrendering to God, praying, recognizing God's greatness, gratitude, and obedience. The conclusion of this study is that the novel Heartbreak Motel by Ika Natassa contains moral values that can be emulated by readers.